2022
DOI: 10.3390/gels8070410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gel Stage from Cellulose Dissolution in NaOH-Water System on the Performances of Cellulose Allomorphs-Based Hydrogels

Abstract: Novel hydrogels were prepared starting from different cellulose allomorphs (cellulose I, II, and III), through a swelling stage in 8.5% NaOH aqueous solution, followed by freezing at low temperature (−30 °C), for 24 h. After thawing at room temperature, the obtained gels were chemical cross-linked with epichlorohydrin (ECH), at 85 °C. The swelling degrees of the hydrogels were investigated, and a complex dependence on the type of the cellulose allomorph was found. Moreover, the gel stage has been shown to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The higher the NaOH concentration, the more cellulose polymer chains are disrupted, resulting in shorter bonds and smaller cross-linking, decreasing pore size. Consequently, the water absorption capacity is reduced [26]. The swelling degree in PBS solution exhibits a significantly higher value compared to distilled water, while following the same trend of reduction with increasing NaOH fraction, as depicted in Figure 4 (b).…”
Section: Swelling Degree and Weight Lossmentioning
confidence: 76%
See 3 more Smart Citations
“…The higher the NaOH concentration, the more cellulose polymer chains are disrupted, resulting in shorter bonds and smaller cross-linking, decreasing pore size. Consequently, the water absorption capacity is reduced [26]. The swelling degree in PBS solution exhibits a significantly higher value compared to distilled water, while following the same trend of reduction with increasing NaOH fraction, as depicted in Figure 4 (b).…”
Section: Swelling Degree and Weight Lossmentioning
confidence: 76%
“…It can be observed that increasing the NaOH fraction in the hydrogel leads to a decrease in swelling degree, attributed to the reduction in pore size. Higher weight loss is also observed, indicating a weakening of crosslinking strength between polymer chains [26].…”
Section: Swelling Degree and Weight Lossmentioning
confidence: 98%
See 2 more Smart Citations
“…In comparison, glutaraldehyde raised concerns regarding the potential presence of toxic residues after the reaction [46]. Moreover, the use of citric acid or cellulose crosslinking required an elevated temperature to achieve higher crosslinking efficiency, which may lead to cellulose degradation [47]. Based on the aforementioned factors, EPI is considered a superior crosslinker for hydrogel preparation.…”
Section: Introductionmentioning
confidence: 99%